2004
DOI: 10.1111/j.1600-051x.2004.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular overdentures supported by two Brånemark, IMZ or ITI implants: a 5‐year prospective study

Abstract: It is concluded that two implants placed in the interforaminal region, connected with a bar, supply a proper base for the support of a mandibular overdenture in the edentulous patient. After 5 years no clinically relevant and statistically significant radiographic changes had developed between the three implant systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
62
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 14 publications
12
62
1
1
Order By: Relevance
“…[1][2][3][4][5][6] However, not all implants are successful and some fail as a result of bone loss and inflammatory reactions along the implant-tissue interface. In most cases, failure of loaded implants is accompanied with a gradual process of breakdown of supporting soft and hard tissues.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] However, not all implants are successful and some fail as a result of bone loss and inflammatory reactions along the implant-tissue interface. In most cases, failure of loaded implants is accompanied with a gradual process of breakdown of supporting soft and hard tissues.…”
mentioning
confidence: 99%
“…1 Many studies showed effective results using 2 TPS implants (rather than 4) for supported mandibular overdenture treatment. [2][3][4][5] In conclusion, this study provided additional evidence that 2 implants are as effective as 4 for supporting an overdenture. ; PTV = Periotest value; TPS = titanium plasma-sprayed screw implants (control); SD = standard deviation.…”
Section: Commentary and Analysismentioning
confidence: 83%
“…The mandibular arch was selected for implant placement because problems involving lack of stability and retention were always encountered with mandibular denture [13]. The implants were placed in the region of the cuspids in between the two mental foramina at best bone quality and to avoid injury to the inferior alveolar nerve in the posterior region of the mandible.…”
Section: Discussionmentioning
confidence: 99%